Description Of Hemodynamic Status Of Conscious Extubation Of Patients With Tonsillectomy Procedures Using General Anesthesia - Cili Rohyaji; Tati Hardiyani (CV. AFDIFAL MAJU BERKAH, 2026)
Post-tonsillectomy awake extubation under general anesthesia has the potential to trigger hemodynamic fluctuations due to sympathetic stimulation, but prospective data in the Indonesian context is still limited. This study aims to describe the hemodynamic status in the post awake extubation period in tonsillectomy patients. Using a descriptive quantitative design, the population included 29 patients aged 12–35 years at Wijayakusuma Hospital III Purwokerto (December 2025–January 2026) with total sampling. Primary data were measured via bedside monitors and observation sheets, and univariate analysis was performed using SPSS. The results showed that the majority of respondents were 17–25 years old (51.7%) and female (65.5%). In the post-awake extubation period, hemodynamic findings demonstrated pre-hypertensive systolic and diastolic blood pressure (44.8% and 55.2%, ), while mean arterial pressure (79.3%), pulse rate (62.1%), respiratory rate (75.9%), and oxygen saturation (100%) remained within normal limits.